Reversal Of Arterial Disease by modulating Magnesium and Phosphate (ROADMAP-study): rationale and design of a randomized controlled trial assessing the effects of magnesium citrate supplementation and phosphate-binding therapy on arterial stiffness in moderate chronic kidney disease - Emma A. Vermeulen; Coby Eelderink; Tiny Hoekstra; Adriana J. van Ballegooijen; Pieter Raijmakers; Joline W. Beulens; Martin H. de Borst; Marc G. Vervloet (Trials, 2022)
Abstract Background Arterial stiffness and calcification propensity are associated with high cardiovascular risk and increased mortality in chronic kidney disease (CKD). Both magnesium and phosphate are recognized as modulators of vascular calcification and chronic inflammation, both features of CKD that contribute to arterial stiffness. In this paper, we outline the rationale and design of a randomized controlled trial (RCT) investigating whether 24 weeks of oral magnesium supplementation with or without additional phosphate-binding therapy can improve arterial stiffness and calcification propensity in patients with stage 3–4 CKD. Methods In this multi-center, placebo-controlled RCT, a total of 180 participants with an estimated glomerular filtration rate of 15 to 50 ml/min/1.73 m2 without phosphate binder therapy will be recruited. During the 24 weeks intervention, participants will be randomized to one of four intervention groups to receive either magnesium citrate (350 mg elemental magnesium/day) or placebo, with or without the addition of the phosphate binder sucroferric oxyhydroxide (1000 mg/day). Primary outcome of the study is the change of arterial stiffness measured by the carotid-femoral pulse wave velocity over 24 weeks. Secondary outcomes include markers of calcification and inflammation, among others calcification propensity (T50) and high-sensitivity C-reactive protein. As explorative endpoints, repeated 18F-FDG and 18F-NaF PET-scans will be performed in a subset of participants (n = 40). Measurements of primary and secondary endpoints are performed at baseline, 12 and 24 weeks. Discussion The combined intervention of magnesium citrate supplementation and phosphate-lowering therapy with sucroferric oxyhydroxide, in stage 3–4 CKD patients without overt hyperphosphatemia, aims to modulate the complex and deregulated mineral metabolism leading to vascular calcification and arterial stiffness and to establish to what extent this is mediated by T50 changes. The results of this combined intervention may contribute to future early interventions for CKD patients to reduce the risk of CVD and mortality. Trial registration Netherlands Trial Register, NL8252 (registered December 2019), EU clinical Trial Register 2019-001306-23 (registered November 2019).